Feasibility of preoperative and postoperative physical rehabilitation for cardiac surgery patients - a longitudinal cohort study - Sandra Dijkstra; Johanneke Hartog; Joke Fleer; Pim van der Harst; Lucas H.V. van der Woude; Massimo A. Mariani (BMC, 2023)
Abstract Background This study aimed to determine the feasibility of a preoperative and postoperative (in- and outpatient) physical rehabilitation program, the Heart-ROCQ-pilot program. Methods This cohort study included patients undergoing cardiac surgery (including coronary artery bypass graft surgery, valve surgery, aortic surgery, or combinations of these surgeries) and participated in the Heart-ROCQ-pilot program. Feasibility involved compliance and characteristics of bicycle and strength training sessions in the three rehabilitation phases. Results Of the eligible patients, 56% (n = 74) participated in the program (41% of exclusions were due to various health reasons). On average across the rehabilitation phases, the compliance rates of bicycle and strength training were 88% and 83%, respectively. Workload to heart rate (W/HR) ratio and total absolute volume load for bicycle and strength training, respectively, improved in each rehabilitation phase (P < 0.05). The W/HR-ratio was higher during the last postoperative session compared to the first preoperative session (0.48 to 0.63 W/beat, P < 0.001) and similar to the last preoperative session (0.65 to 0.64 W/beat, P < 0.497). During less than 1% of the bicycle sessions, patients reported discomfort scores of 5 to 6 (scale 0-10, with higher scores indicating a higher level). Conclusions The Heart-ROCQ-pilot program was feasible for patients awaiting cardiac surgery. Patients were very compliant and were able to safely increase the training load before surgery and regained this improvement within eight weeks after surgery.